A systematic review and meta-analysis on the impact of pre-existing and new-onset atrial fibrillation on outcomes before and after liver transplantation. Issue 5 (May 2022) - So, Wei Zheng; Tan, Felicia Liying; Tan, Darren Jun Hao; Ng, Cheng Han; Yong, Jie Ning; Syn, Nicholas; Tang, Ansel Shao Pin; Wong, Raymond C; Lin, Weiqin; Tan, Eunice Xiang Xuan; Huang, Daniel Q.; Dan, Yock Young; et al.
Abstract: Background and aims: Atrial Fibrillation (AF) is the most commonly diagnosed cardiac arrhythmia. It is associated with significant morbidity and mortality, as it is a major risk factor for cerebral vascular accidents (CVA). Our aim was to determine the prevalence of pre-existing and new-onset AF among patients undergoing liver transplantation (LT) and its impact on post-transplant outcomes. Methods: Medline and Embase were searched. Single-arm analysis was conducted using the generalized linear mixed model to determine the prevalence of pre-existing and new-onset AF. Logistic regression was performed to analyze risk factors. Comparative meta-analysis in odds ratio was conducted for binary outcomes. Results: Twenty articles were included, with 17 studies on pre-existing AF, and 7 including data on new-onset AF post-LT. The prevalence of pre-existing AF was 3.3% (CI 2.3–4.7) (14 studies, 45, 070 patients) in pooled analysis. Significantly higher prevalence of pre-existing AF patients from North America was noted when compared to Europe (4.5%, CI 3.4–5.8 vs 1.5%, CI 0.8–2.7; p = 0.001). Body mass index (BMI), history of hypertension, diabetes, coronary artery disease (CAD), and cerebrovascular accidents (CVA) were risk factors for pre-existing AF. Pre-existing AF was significantly associated with major adverse cardiac or cerebrovascular events (MACCE) postoperatively (OR 8.02, 95%CI 5.40–11.90, p < 0.001). New-onset AF post-LT had an incidence of 6.8% (CI 4.9–9.3), and was associated with increased risk of mortality (OR 2.31, 95% CI 1.76–3.02, p < 0.001) and graft failure (OR 2.98, CI 1.99–4.47, p < 0.001). Conclusion: AF is relatively more common among patients undergoing LT compared to the general non-transplant population. Additionally, it is associated with adverse outcomes including MACCE, thus warranting clinical attention. Thorough cardiac assessment, and close surveillance of post-operative AF may be clinically prudent.